Топометрическая характеристика послойного строения чешуи затылочной кости - О.Ю. Вовк; А.А. Шмаргалев; В.Б. Икрамов; К.Д. Ткаченко; Ю.В. Богуславский; О.В. Редякина (Експериментальна і клінічна медицина, 1970)
УДК 611.714.3О.Ю. Вовк, А.А. Шмаргалев, В.Б. Икрамов, К.Д. Ткаченко, Ю.В. Богуславский, О.В. РедякинаГЗ «Луганский государственный медицинский университет»ТОПОМЕТРИЧЕСКАЯ ХАРАКТЕРИСТИКА ПОСЛОЙНОГО СТРОЕНИЯ ЧЕШУИ ЗАТЫЛОЧНОЙ КОСТИПриведена детальная морфометрическая характеристика изменчивости толщины чешуи затылочной кости и ее структурных слоев с учетом рельефной топографии. Полученные данные могут быть использованы в нейрохирургической практике для более точного выбора места фиксации металлических конструкций при окципитоцервикаль ном остеосинтезе.Ключевые слова: затылочная кость, краниотопография, череп, диплоэ.О.Ю. Вовк, А.О. Шмаргальов, К.Д. Ткаченко, В.Б. Ікрамов, Ю.В. Богуславський, О.В. РедякінаТОПОМЕТРИЧНА ХАРАКТЕРИСТИКА ПОШАРОВОЇ БУДОВИ ЛУСКИ ПОТИЛИЧНОЇ КІСТКИНаведена детальна морфометрична характеристика мінливості товщини луски потиличної кістки і її структурних шарів з урахуванням рельєфної топографії. Наведені дані можуть бути використані в нейрохірургічній практиці для більш точного вибору місця фіксації металевих конструкцій при окципітоцервікальному остеосинтезі.Ключові слова: потилична кістка, краніотопографія, череп, діплое.O.Yu. Vovk, A.A. Shmargalev, K.D. Tkachenko, V.B. Ikramov, Yu.V. Boguslavsky, O.V. RedyakinаMORPHOMETRIC CHARACTERISTIC OF THE LAYERWISE STRUCTURE OF SQUAMOUS PART OF THE OCCIPITAL BONEThe article is a detailed morphometric characteristics of thicknes variability of squamous part of the occipital bone and its structural layers with the relief topography. The study involved serial bone sections of 100 (61 male and 39 female) skulls of adults. Longitudinal cuts of the occipital bone using a specially designed «devices for making bone cuts» were performed. Layerwise occipital bone structure is characterized by individual anatomical variability of its external and internal relief. Total thickness increases in external occipital protrusion (10.8-20.3 mm) along the top and the nuchal line (4.5-11.8 mm) minimum thickness (0.1-1.5 mm) in centers cerebellar and cerebral fossa.The outer plate generally follows the distribution of the total thickness of the bone, and an inner thin stably over the whole area. In thin places of bone diploe disappears, and the outer and inner layers of the compact substance are combined into one. Planned to further study the topography of the occipital bone, taking into account the shape of occipital bone and of the skull shape, age and gender.Obtained data can be used in neurosurgical practice for more accurate choice of fixing structures at occipito-cervical osteosynthesis. These data may be useful for neurosurgeons, pathologists, anthropologists.Key words: occipital bone, craniotopography, skull, diploe.Поступила 26.03.14